ANALISIS SOSIAL EKONOMI PEMBANGUNAN MASYARAKAT INDRAMAYU - Sumarta Sumarta; Abas Abdul Jalil (LPPM STAIS Dharma Indramayu, 2022)
Indramayu is a very fertile area due to the presence and passage of the Cimanuk river which has an impact on soil fertility which is very serviceable and suitable for development and growth in agriculture. With a historical approach method with literature study and interview methods can construct how the socio-economic development of the Indramayu community in its journey from time to time. The problem of hard work no longer needs to be questioned to see the phenomenon of Socio-Economic Development in Indramayu Regency which focuses on the dynamics that occur in the firecracker industry, people's salt, women's labor and agriculture. They try to deal with various obstacles, challenges, opportunities and changes that occur from their perspective, even though they often intersect with rules or other parties and even the existing culture.